Variability in soil physical properties in landslide-prone areas (Acta Scientiarum. Agronomy, 2017)
The present study aimed to evaluate the relationship between the physical properties of the soil and relief in areas that are susceptible to landslides in the sub-basin of the Córrego do Yung, a creek in the urban district Três Moinhos of Juiz de Fora, Minas Gerais. Depth measurements of the solum were made at the soil sampling points, and the subsurface material was collected and analyzed for the two factors of particle size and type of horizon. In the laboratory, we determined the hydraulic conductivity, bulk and particle density, and total porosity, macroporosity and microporosity. The values of the physical properties throughout the sub-basin were predicted and mapped. Thematic maps were generated and showed a relation to each other: the clay was related to a higher hydraulic conductivity, higher porosity and lower soil density. In the steeper areas, the greater silt contents were mapped in the deeper layers and indicated the thin thickness of horizon B in these areas. A close relation of the curvature with the soil thickness was detected and was greater in the flat areas with less slope. The geostatistical analysis showed that the range of values for the properties of macroporosity, microporosity and silt was the lowest in the deeper layers, indicating low structural continuity in potentially erodible areas.